Arete and sophia dans le traité de De uirtute morali de Plutarque - Pinheiro, Joaquim (2020)
Taking as a starting point the ethical and psychological argumentation that Plutarch develops in the treatise De uirtute morali, this paper will propose a double reflection on the complex relation between arete and sophia. On the one hand, the focus of interest will be the theoretical dimension of these concepts. On the other hand, it will be the realization of virtue in and through action. It will thus be necessary to underline the contribution of this treatise to the setting up of the figure of the ideal politician: one who participates actively in political action, but does so while implementing wisdom (sophia and phronesis, depending on the circumstances).